Longitudinal assessment of metal concentrations and copper isotope ratios in the G93A SOD1 mouse model of amyotrophic lateral sclerosis. Issue 2 (9th January 2017) - Enge, T. Gabriel; Ecroyd, Heath; Jolley, Dianne F.; Yerbury, Justin J.; Dosseto, Anthony
Abstract : Muscle tissue may play an important role in the aetiology of amyotrophic lateral sclerosis, where accumulation in the tissue may aid in the development of the disease. Abstract : Amyotrophic lateral sclerosis (ALS) is a motor neuron disease, which involves progressive motor neuron degeneration in the central nervous system (CNS). The G93A SOD1 mouse model simulates one of the most common causes of familial ALS through the overexpression of a mutated form of the human gene encoding copper/zinc superoxide dismutase (SOD1). Transition metals, particularly Cu and Zn, have been shown to behave abnormally in the disease context and have been hypothesized to contribute to and potentially trigger the disease. In this study, concentrations of Cu, Zn and Fe, as well as Cu isotope ratios were assessed in keystone tissues of ALS, including the brain, spinal cord, muscle and whole blood, from transgenic mutant SOD1 G93A mice and non-transgenic controls. While no consistent Cu isotope signal was found to be related to the disease state, concentrations of Cu, Zn and Fe were significantly elevated in muscle tissue of the transgenic mice, even at pre-symptomatic time points. In brain and muscle tissue, in both animal groups, a time-dependent Cu isotope signal was observed. We hypothesize that the early and significant elevation in metal concentration in muscle tissue from SOD1 transgenic mice could facilitate the development of ALS, without affecting the overall signal from well-buffered CNS tissues. Ageing may be recorded isotopically as a shift from a neonatal Cu pool as inherited from the mother, through dietary Cu and recycling processes.